Interval Valued Picture Fuzzy Aczel–Alsina Aggregation Operators and Their Application by Using the Multiattribute Decision Making Problem - Khalida Jabeen; Kifayat Ullah; Maria Akram; Izatmand Haleemzai (Journal of Mathematics)
The engineering and construction sector is vital to a country’s economic growth, financial activities, and development. These sectors generate opportunities for the unemployed, unskilled, and skilled workforce. Recently, a lot of researchers worked on the Aczel–Alsina t-norm (TN) and t-conorm (TCN), which are generalizing many other t-norms and producing reliable results. In this article, first, we developed some new aggregation operators (AOs) and fundamental operational laws of Aczel–Alsina operations, including Aczel–Alsina product, sum, and scalar multiplication based on the IVPF information. Furthermore, we introduced an innovative AOs in the form of IVPF Aczel–Alsina weighted averaging (IVPFAAWA) operators with some basic characteristics. Moreover, we also generalized Aczel–Alsina operations in the form of the IVPF Aczel–Alsina weighted geometric (IVPFAAWG) operator. For the solution of daily life problems by utilizing a multiattribute decision-making (MADM) approach, we also established an application under the system of engineering and construction sectors. We illustrated a numerical example to find the suitable construction material for the engineering and construction sectors. To find the validity and flexibility of our proposed AOs, we also studied a comprehensive comparative analysis, in which we compared the results of exiting AOs with the results of our current invented approaches. At the end, we sum up our whole article in a single paragraph.